Apoptotic death of neurons СА-1 zone of hippocampus of rats in the condition of prenatal chronic alcoholisation and their reduction by cerebrocurin and tiocetam - Sokolik, Elena; Okoli, Mark-Entony; Faseun, Omonike Ibukun (Запорізький державний медичний університет, 2015)
Our research found that prenatal alcoholism leads to increase of NO induction and nitrosine stress in the brain of newborn rats, evidenced by the increasing of nitrotyrosine in citosole and mitochondria. By adjusting the ratio of mitochondrial/cytosole concentrations of NO and reactive oxygen forms, cerebrocurin and tiocetam limited the effect of these compounds on the activation or deprivation of the processes of gene expression, transcription and translation in neuronal cells of brain of animals that survived the prenatal alcoholism and, thus, may provide the normal development of the cognitive functions of central nervous system.